Longitudinal data on employee attitudes and personality in activity-based work environmentsMendeley Data - Freyr Halldorsson; Halldor Valgeirsson; Kari Kristinsson (Data in Brief)
Longitudinal data were collected from two smaller organizations implementing activity-based work environments. The sample consisted of a total of 50 employees, with each employee being surveyed four times. The initial survey took place a month before the activity-based work environment was implemented, followed by measures one, six, and 12 months after implementation. At each measurement point, the response rate was 58–76 %, providing a total of 130 observations. All data were collected using an online survey, with participants receiving a link via email followed up with two reminders. Each survey contained the same questions, except for the personality items, which were only included in the first survey. Participation was voluntary, and participants consented to take part. No incentives were provided for participating.